Assessment of Alumina Nanofluid as a Coolant in Double Pipe Gas Cooler for Trans-critical CO2 Refrigeration Cycle. (March 2017) - Purohit, Nilesh; Khangarot, Balraj Singh; Gullo, Paride; Purohit, Kamlesh; Dasgupta, Mani Sankar
Abstract: In this study, the performance of an alumina nanofluid cooled double pipe gas cooler for trans-critical CO2 refrigeration cycle is theoretically compared to that of water cooled gas cooler. Equal pumping power comparison criterion is adopted besides conventional equal Reynolds number comparison base. Nanofluid is loaded with 0.5%, 1.5% and 2.5% of particle volume fraction under turbulent flow conditions. Drastic variation of thermal and transport properties of CO2 in the vicinity of pseudo critical temperature is taken care of by employing an appropriate discretization technique. Effect of gas cooler pressure, Reynolds number, pumping power and nanoparticle volume fraction on COP of refrigeration system, gas cooler overall conductance, effectiveness and its capacity has been studied. Results indicate that at equal Reynolds number comparison, performance for alumina nanofluid cooled system is better than that of water cooled system. On the other hand, at equal pumping power comparison basis, the performance of water cooled system is superior. Even at equal mass flow rate comparison criterion, the performance of nanofluid cooled system degrades with increase in particle volume fraction. This study is expected to help to assess the nanofluid as a coolant before expensive experimentation.